2023
DOI: 10.1039/d2nj05978a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polymeric surfactant containing bis-cationic motifs as a highly efficient acid corrosion inhibitor for C1018 carbon steel

Abstract: The present study describes the synthesis and characterization of a Poly(methyldiallylammonium chloride)-based surfactant containing bis-cationic motifs 9 by a series of reactions. The synthesized polymer 9 was characterized by FTIR...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Overall, the negative sign associated with the value of ensures that the adsorption process is spontaneous. 19,40…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the negative sign associated with the value of ensures that the adsorption process is spontaneous. 19,40…”
Section: Resultsmentioning
confidence: 99%
“…2 Studies have shown that polymeric surfactants are very effective in arresting corrosion. [15][16][17][18][19] The hydrophilic portions of the surfactants interact with the metal surfaces, and the hydrophobic parts spread out toward the water molecules and repel them. This study explores the mild steel corrosion inhibition efficiency of a homopolymer (3), poly(diallylammonium chloride), and some copolymers (8a-c) containing pyrrolidine ring and a long hydrophobic/hydrophilic cationic pendant (5-20%) moieties (Scheme 1) in a 20% formic acid solution.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of –NH 2 or –OH substituents invokes higher dipole moment for APYBT and HPYBT, which enhances the electrostatic interaction between those molecules and the metal surface. 79 From the optimized geometry of the inhibitor molecules and electronic disposition in the HOMO and LUMO levels, the mode of interaction between the inhibitor and metal is presumed. It is seen that all three BT-Py derivatives are almost planar (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, a longer hydrocarbon chain has the reverse effect on how well it performs after a certain length. [23,24] Their decreased solubility explains this.…”
Section: Introductionmentioning
confidence: 99%
“…This is undoubtedly accurate for surfactant molecules with the ideal size. However, a longer hydrocarbon chain has the reverse effect on how well it performs after a certain length [23,24] . Their decreased solubility explains this.…”
Section: Introductionmentioning
confidence: 99%